Using Fun Learning Method with Iqro' Block Media to Improve the Reading Ability of Paud Hijaiyah Students - Nasita Dara Maula; Umi Machmudah; Ma’rifatul Munjiah; Umi Fahriyah (Jurusan Pendidikan Bahasa Arab, 2023)
Religious education should be introduced to children from an early age. At PAUD KB Ceria Serang, Islamic religious education was introduced to students, one of which was by teaching the hijaiyah letters to students. To improve students' ability to read hijaiyah letters, one of the methods used is to use the iqra' block media. This research is a quantitative research with the type of experimental research with a quasi-experimental design. The population in this study were all students of PAUD KB Pelangi Ceria Serang with a sample of 24 students in class B. Based on the results of data analysis, the average pretest score was 53.21 and the posttest average was 74.46. And based on the independent sample t-test output table in the equal variances assumed section, it is known that the sig2teiled value is 0.000 <0.05, so it can be concluded that there is an increase in students' reading skills ability after using the iqra' beam media.